HUBUNGAN ANTARA KOMITMEN ORGANISASI DAN IKLIM ORGANISASI DENGAN KEPUASAN KERJA KARYAWAN UNIVERSITAS MUHAMMADIYAH SURAKARTA - Satria R.A, R. Yudhi . (Benefit: Jurnal Manajemen dan Bisnis, 2005)
This research objective is to find out the correlation between organizational commitment andorganizational climate with the job satisfaction. Job satisfaction functions as a dependent variable on this research. There are two variablesfunctioning as independent variables, those are the commitment and the climate of organization. Thehypothesis proposed in this research is divided into one major hypothesis, that is the correlation betweenorganizational commitment and organizational climate with the job satisfaction. Two minor hypothesisproposed in the study are the positive correlation between organizational climate with work satisfaction,and the positive correlation between organizational climate with the job satisfaction. The sample of this research is included three hundreds employees of Muhammadiyah University ofSurakarta, acquired by random sampling technique. Data is collected through questionnaire methodand analyzed by regression method. The result of this research indicates that there is a significant correlation between organizationalcommitment and organizational climate with the work satisfaction, while the dominant free variableand the commitment variable becomes the major contributor in affecting the job satisfaction. Theresearch also indicates that there is a positive and significant correlation between organizationalcommitment and the job satisfaction, in which the continuous and the normative factors become thedominant. This research also proves that there is a significant correlation between organizational climatewith the work satisfaction. The dominant factors are conformity and organization clarity. The other result of this research indicates that there is a very significant difference betweenorganizational commitment, organizational climate and the job satisfaction on many work units wherethe employees work.